2014
DOI: 10.1002/hfm.20592
|View full text |Cite
|
Sign up to set email alerts
|

Display Movement Velocity and Dynamic Visual Search Performance

Abstract: In practice, many visual search tasks are performed under dynamic conditions. An experiment was conducted here to test visual search strategy adopted by a person in a dynamic visual search and to investigate the effects of display movement velocity on search time and detection accuracy in it. Thirty‐five participants were randomly tested with all 10 angular velocities of 0, 2, 4, 6, 8, 10, 12, 14, 16, and 32 deg/s. The data obtained fitted the random search model well. The results revealed that observers utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…Target images were black standard Landolt Cs with four orientations (up, down, left, and right). Previous research results showed that Landolt Cs with four orientations presented the same difficulties in visual search tasks (Yu & Chan, ). The type of target images was randomly selected by the software.…”
Section: Methodsmentioning
confidence: 78%
“…Target images were black standard Landolt Cs with four orientations (up, down, left, and right). Previous research results showed that Landolt Cs with four orientations presented the same difficulties in visual search tasks (Yu & Chan, ). The type of target images was randomly selected by the software.…”
Section: Methodsmentioning
confidence: 78%
“…Visual search capacity can be defined in terms of the percentage of targets detected against the time consumed. Theoretically, the RSM is captured by an exponential curve, while the systematic model is captured by a linear function [19,21]. In addition, when the background area is larger than the search target, observers tend to follow the random search strategy [20,21,23].…”
Section: Rsm For Inspection Efficiencymentioning
confidence: 99%
“…Apart from that, previous studies on the RSM mainly focused on exploring the performance of the RSM in various scenarios. Yu et al [19] found that the traditional RSM performed very well on static visual search tasks under dynamic conditions. Chan et al [20] used the RSM for a double-target search task and the results showed that the RSM fitted both the individual and pooled data very well.…”
Section: Rsm For Inspection Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Many electronic and mechanical components used in consumer products have been miniaturized, so much so that magnification is now a commonly applied means of improving task visibility in quality inspection tasks. There have been many studies on visual search (Sarac, Batta, & Drury, ; Shive & Francis, ) and visual inspection (Chan & Ng, ; Kotani, Nakajima, Asao, & Horii, ; C. L. Lin, Chen, Twu, & Wang, ; L. T. Lin, Liang, Hwang, & Wang, ; Rao, Bowling, Khasawneh, Gramopadhye, & Melloy, ; Tetteh, Jiang, Mountjoy, Seong, & McBride, ; Jiang, Gramopadhye, Melloy, & Grimes, ; Yu & Chan, in press) over the past 50 years or so (Erickson, ; Krendel & Wodinsky, ). These studies include examination of human search performance under different test conditions, such as level of background luminance, contrast, and the presence of glare; the relationship between search time and peripheral visual acuity; visual field mapping; the effects of training and job aids on visual inspection; the modeling of visual search; and the application of visual search model to map display design.…”
Section: Introductionmentioning
confidence: 99%